Harmful Roles of TLR3 and TLR9 in Cardiac Dysfunction Developing during Polymicrobial Sepsis. (30th September 2018) - Fattahi, Fatemeh; Russell, Mark W.; Malan, Elizabeth A.; Parlett, Michella; Abe, Elizabeth; Zetoune, Firas S.; Ward, Peter A.
Abstract : We determined the roles of TLR3 and TLR9 in adverse events of polymicrobial sepsis, with a focus on development of septic cardiomyopathy, progression of which we have recently shown to be complement- and histones-dependent. So Wt, TLR3-knocked out (K.O.), and TLR9-K.O. mice were subjected to polymicrobial sepsis following cecal ligation and puncture (CLP). In the absence of either TLR3 or TLR9, the intensity of echocardiogram (Echo)-Doppler dysfunction during development of cardiomyopathy was substantially reduced in the K.O. mice. Based on our prior studies emphasizing the adverse effects of plasma C5a and histones in the cardiomyopathy of sepsis, in TLR3- and TLR9-K.O. mice, there were striking reductions in plasma levels of C5a and histones as well as reduced levels of cytokines in plasma and heart tissue after CLP. Since we know that histones cause cardiac dysfunction, rat cardiomyocytes (CMs) were exposed in vitro to the histones (purified from calf thymus), which caused bleb formation on the surfaces of CMs, suggesting histones may perturb the cell membrane of CMs. In vitro, exposure of CMs to the histones for 3 hours caused lactate dehydrogenase release from CMs. These data indicate that sepsis-induced cardiac dysfunction requires presence of TLR3 and TLR9 and may be linked to histone-induced damage of CMs.